2016
DOI: 10.1532/hsf.1577
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Low Serum Albumin Levels Increase the Requirement of Renal Replacement Therapy after Cardiac Surgery

Abstract: Low preoperative serum albumin levels result in severe acute kidney injury and increase the rate of renal replacement therapy and mortality after isolated CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Therefore, the antioxidant properties of albumin 154 make it an attractive option for use in cardiac surgery settings, although no RCTs have shown improved outcomes directly due to the oxygen radical scavenging properties of albumin. Hypoalbuminemia has been associated with AKI and need for RRT in the cardiac surgery population [155][156][157][158] . In patients with hypoalbuminemia undergoing off-pump coronary artery bypass graft procedures, preoperative treatment with 20% HSA solution reduced the incidence of postoperative AKI versus treatment with saline alone, but this study does not establish that albumin prevents lipid peroxidation of oxygen free radicals, nor rule out that an increased chloride load with saline alone may have led to hyperchloremic acidosis and decreased renal blood flow 159 .…”
Section: Human Albumin Solution For Renal Protectionmentioning
confidence: 99%
“…Therefore, the antioxidant properties of albumin 154 make it an attractive option for use in cardiac surgery settings, although no RCTs have shown improved outcomes directly due to the oxygen radical scavenging properties of albumin. Hypoalbuminemia has been associated with AKI and need for RRT in the cardiac surgery population [155][156][157][158] . In patients with hypoalbuminemia undergoing off-pump coronary artery bypass graft procedures, preoperative treatment with 20% HSA solution reduced the incidence of postoperative AKI versus treatment with saline alone, but this study does not establish that albumin prevents lipid peroxidation of oxygen free radicals, nor rule out that an increased chloride load with saline alone may have led to hyperchloremic acidosis and decreased renal blood flow 159 .…”
Section: Human Albumin Solution For Renal Protectionmentioning
confidence: 99%
“…Findik et al[15] recently performed a retrospective review of data collected prospectively from 530 adults with normal renal function who underwent isolated CAB surgery. Their analysis divided the patient population based on preoperative serum albumin level and found that RRT ( P = 0.018) and death within 30 d (6.8% vs 2.4%; P = 0.037) after surgery were more frequent in the group with albumin < 3.5 g/dL.…”
Section: Cardiac Surgery and Acute Coronary Interventionsmentioning
confidence: 99%
“…Cumulative evidence have shown that hypoalbuminemia is an important risk factor for postoperative AKI in various clinical settings [8][9][10][11][12]. However, in surgical settings, studies were mainly focused on cardiac surgery and transplant surgery [11,12,[21][22][23]. Few studies have examined the effect of preoperative hypoalbuminemia on postoperative AKI patients undergoing non-cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%